Bridging Home and School Literacies: A Sociocultural Analysis of Early Literacy Practices in Rural Indonesia - Afdhal, Afdhal (Jurnal Tahuri, 2023)
This study examines the sociocultural dimensions of early literacy practices in rural Indonesia, addressing the limited understanding of how home and community literacies intersect with formal schooling in marginalized contexts. Despite national efforts promoting standardized literacy instruction in Bahasa Indonesia, children’s literacy development in Negeri Suli, Central Maluku, remains deeply shaped by the social, cultural, and religious life of the community. The study aims to explore how home, church, and school literacy events interact and how these interactions influence children’s early reading and writing experiences. Employing a qualitative ethnographic design, data were gathered through classroom and home observations, semi-structured interviews with teachers, parents, and Sunday school leaders, and analysis of local literacy artifacts. The findings reveal that literacy learning in Suli is primarily cultivated through religious and communal activities such as home prayers and church gatherings, which contrast sharply with the print-based, decontextualized literacy valued in schools. This discontinuity marginalizes children’s home literacies and limits their classroom engagement. The study’s novelty lies in situating sociocultural literacy theory within a non-Javanese, rural Christian community, highlighting faith and collective life as mediating forces in literacy development. Theoretically, it expands global understandings of literacy as a culturally situated practice, and practically, it informs inclusive, community-based pedagogical models for literacy education in diverse Indonesian contexts.